Distinct patterns of comorbidity prior to diagnosis of incident systemic lupus erythematosus in the Danish population. Issue 123 (September 2021) - Hansen, Renata Baronaite; Simard, Julia F.; Faurschou, Mikkel; Jacobsen, Søren
Abstract: The objective of this study was to assess the cumulative prevalence of pre-existing comorbidities among patients diagnosed with systemic lupus erythematosus (SLE) in Denmark. The study included patients aged ≥18 years at the index date set to the date of first registration of SLE in the Danish National Patient Registry (DNPR) between 1996 and 2018. Up to 19 age- and sex-matched general population comparators per case were selected. Comorbidity diagnoses were retrieved from the DNPR based on International Classification of Diseases codes. We estimated cumulative prevalence of various comorbidities among cases and comparators, prevalence differences (PDs), and prevalence ratios (PRs), with PDs and PRs adjusted for age and sex, at the index date and 1, 2, 5, and 10 years before the index date. We identified 3, 010 SLE cases and 57, 046 comparators (mean age at index date: 47.3 years). Most comorbidities occurred more often in SLE patients versus comparators at the index date and up to 10 years before. Overrepresented comorbidities in SLE patients 10 years before SLE diagnosis included neuropsychiatric, cardiovascular, and venous thromboembolic diseases; PDs (95% CI) were 2.3% (1.4–3.3%), 1.3% (0.6–1.9%), and 1.1% (0.6–1.5%), respectively; corresponding PRs (95% CI) were 1.5 (1.3–1.8), 1.7 (1.4–2.1), and 4.3 (3.1–6.1). We found a higher prevalence of multiple comorbidities—not only at the time of SLE diagnosis but likewise during the 10-year pre-diagnosis period—among individuals with SLE. These findings underscore the importance of early clinical vigilance toward comorbidities starting in the diagnostic phase of SLE. Highlights: Few studies have addressed progression patterns of comorbidity before SLE diagnosis. A higher comorbidity prevalence was found in SLE patients versus general population. Increase in comorbidities was seen up to 10 years before and at SLE diagnosis. The importance of screening for comorbidities at SLE diagnosis is highlighted.